Power System State Estimation Approach Considering Transmission Line Temperature - Qingwen Xu; Hengxu Zhang; Yongji Cao; Hao Qin; Zhimin Gao (Applied Sciences, 2022)
The transmission line parameters vary with the change of temperature, which has a significant impact on power system state estimation (SE). Based on the theory of electro-thermal coordination (ETC), this paper proposes two ETC-SE approaches with the consideration of transmission line temperature. The heat balance equation (HBE) is combined with the conventional weighted least square SE for establishing an ETC-SE model. Moreover, an augmented Jacobian ETC-SE approach is developed by integrating the HBE into pseudo measurements and the line temperature into state vectors. The Jacobian matrix is augmented correspondingly and the partial differential coefficients of measurements to line temperature are provided, which enables to calculate line temperature and voltage phasors simultaneously. Furthermore, in order to accelerate the solving process, an improved two-step ETC-SE algorithm is proposed, in which the SE and temperature estimation are decoupled and solved via alternate iteration. The effectiveness of the proposed ETC-SE approaches is verified by the IEEE 14-, 39-, and 118-bus systems. The results show that the proposed ETC-SE approach is effective to reduce the calculation errors and possesses good convergence performance with varying environmental circumstances and ill-conditioned branches.